Biopharmaceuticals in plants : toward the next century of medicine - Hefferon, Kathleen L. (Boca Raton : CRC Press, 2010)
'Transgenic plants present enormous potential to become one of the most cost-effective and safe systems for large-scale production of proteins for industrial, pharmaceutical, veterinary, and agricultural uses. Over the past decade, much progress has been made with respect to the development of vaccines, antibodies, and other therapeutic proteins. Biopharmaceuticals in Plants: Toward the Next Century of Medicine provides a comprehensive survey of all major aspects of the development and production of plant-made biopharmaceuticals.'--Publisher's description.
History of plants in production of biopharmaceuticals -- Transgenic plants expressing vaccine and therapeutic proteins -- Chloroplast engineering and production of biopharmaceuticals -- Plant viral expression vectors and production of biopharmaceuticals in plants -- Glycosylation of therapeutic proteins in plants -- Scale-up of plant-derived pharmaceuticals : prospects for commercial production and for global health -- The immune response to plant-derived biopharmaceuticals -- Risk analysis and safety of plant-made biopharmaceuticals -- Epilogue : the future.
Keywords: Gene Expression Regulation, Plant; Plant Extracts; Technology, Pharmaceutical